Synthesis and In Vivo Antiarrhythmic Activity Evaluation of Novel Scutellarein Analogues as Voltage-Gated Nav1.5 and Cav1.2 Channels Blockers - Wei Yang; Wenping Wang; Song Cai; Peng Li; Die Zhang; Jinhua Ning; Jin Ke; Anguo Hou; Linyun Chen; Yunshu Ma; Wenbin Jin (Molecules, 2023)
Malignant cardiac arrhythmias with high morbidity and mortality have posed a significant threat to our human health. Scutellarein, a metabolite of Scutellarin which is isolated from Scutellaria altissima L., presents excellent therapeutic effects on cardiovascular diseases and could further be metabolized into methylated forms. A series of 22 new scutellarein derivatives with hydroxyl-substitution based on the scutellarin metabolite in vivo was designed, synthesized via the conjugation of the scutellarein scaffold with pharmacophores of FDA-approved antiarrhythmic medications and evaluated for their antiarrhythmic activity through the analyzation of the rat number of arrhythmia recovery, corresponding to the recovery time and maintenance time in the rat model of barium chloride-induced arrhythmia, as well as the cumulative dosage of aconitine required to induce VP, VT, VF and CA in the rat model of aconitine-induced arrhythmia. All designed compounds could shorten the time of the arrhythmia continuum induced by barium chloride, indicating that 4′-hydroxy substituents of scutellarein had rapid-onset antiarrhythmic effects. In addition, nearly all of the compounds could normalize the HR, RR, QRS, QT and QTc interval, as well as the P/T waves’ amplitude. The most promising compound 10e showed the best antiarrhythmic activity with long-term efficacy and extremely low cytotoxicity, better than the positive control scutellarein. This result was also approved by the computational docking simulation. Most importantly, patch clamp measurements on Nav1.5 and Cav1.2 channels indicated that compound 10e was able to reduce the INa and ICa in a concentration-dependent manner and left-shifted the inactivation curve of Nav1.5. Taken together, all compounds were considered to be antiarrhythmic. Compound 10e even showed no proarrhythmic effect and could be classified as Ib Vaughan Williams antiarrhythmic agents. What is more, compound 10e did not block the hERG potassium channel which highly associated with cardiotoxicity.